2016
DOI: 10.3329/bjvm.v13i2.26632
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Commercially Packaged Sachet Water and the Public Health Implications: An Overview

Abstract: Quality water should be colourless, tasteless, odourless and free from faecal contamination. This study investigates the level of contamination of commercially vended packaged water and their public health implications. Published baseline information and data were used in the study. Using different isolation techniques, coliform bacteria of up to 100% and faecal contamination of up to 40% were reported. The consumption of contaminated commercially packaged water by the public has led to different disease condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 23 publications
2
30
2
1
Order By: Relevance
“…Water is an important component of every life [ 1 – 4 ]. Water supply and accessibility is goal 6 of the sustainable development goals (SDGs) and aims at ensuring environmental sustainability [ 3 , 4 ]. Historically, efforts to ensure access to safe drinking and food processing water have been focused on the community based water sources [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Water is an important component of every life [ 1 – 4 ]. Water supply and accessibility is goal 6 of the sustainable development goals (SDGs) and aims at ensuring environmental sustainability [ 3 , 4 ]. Historically, efforts to ensure access to safe drinking and food processing water have been focused on the community based water sources [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a bid to promote healthy living among inhabitants of the county, a reliable potable water access is essential for sustainable development, health, food production, and poverty alleviation [ 4 , 10 ]. Water shortage and pollution of the readily accessible water sources are evident in many regions of the developing nations [ 3 , 6 , 11 ]. This is largely attributed to low level of personal hygiene and inadequate treatment facilities for water and wastes that are consequent pollutants [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This Pseudomonas finding signals a need for quality control to refocus on equipment maintenance and hygiene, an approach that may require technical and behavioral changes within the production process . With over six times Ghana's population, Nigeria has experienced slower industry maturation and greater regulatory challenges, and thus, we continue to see poor sachet quality reflected in Nigerian studies as demonstrated in a 2015 review of case reports primarily from Nigeria, but also including Ghana, India, and Egypt …”
Section: Product Qualitymentioning
confidence: 99%